THE RELATIONSHIP BETWEEN BLOOD FLOW IN THE CAROTID ARTERY AND SOME MENTAL PROCESSES AND THE ACCURACY OF SKILL PERFORMANCE WITH A TENNIS BALL - Asst. Lect Ayman Abde Kariz; Prof. Dr Ammar Jassim Muslim; Prof. Dr Makki Jabbar Almajdy (Scholars Digest Publishing, 2025)
The research aims to relate the blood flowing in the carotid artery to some mental processes and the accuracy of skill performance with a tennis ball. The experimental method was used and the research community was represented by the (10) players of the Tennis Association in Maysan. The researchers used pre- and post-tests and measurements, which are in line with the research requirements.The results of the study indicated the following: The effect of blood flowing in the carotid artery on some mental processes and the accuracy of skill performance among tennis players in an effective manner among individuals in the experimental group. The most important conclusions were that there is a correlation between the diameter of the carotid artery and the amount of blood flowing in it with some mental processes and accuracy of skill performance with the tennis ball. The researchers recommended the need to conduct studies on other activities because this method has positive results in creating physiological adaptations and improving performance.
Keywords: Blood measurements, carotid artery diameter, accuracy of skill performance.